Oviposition responses of Bactrocera dorsalis and Ceratitis cosyra to Dufour's and poison gland extracts of Oecophylla longinoda (Hymenoptera: Formicidae) - (:unkn) unknown (My University, 2021)
The predatory African weaver ant, Oecophylla longinoda (Hymenoptera: Formicidae) effectively control pests by predation as well as by semiochemicals which influence the behaviour of certain species. Here, we investigated and compared the role of O. longinoda semiochemicals on the oviposition responses of two major fruit fly (Diptera: Tephritidae) species of mango; the invasive species, Bactrocera dorsalis, endemic to Southeast Asia and the African native species, Ceratitis cosyra. We carried oviposition choice assays with ant-exposed and unexposed mangoes, using extracts of ant whole body and body parts. Our results show that the flies avoided and laid fewer eggs on weaver ant-exposed than unexposed mango peel discs. Subsequent assays with mango discs treated with whole body extracts in hexane, ethyl acetate, methanol and water reduced oviposition responses in C. cosyra. Moreover, discs treated with abdominal extracts in hexane and water reduced egg laying in B. dorsalis. whereas hexane, methanol and water extracts of the abdomen reduced oviposition in C. cosyra. Additionally, mango discs treated with extracts of exercised Dufour's and poison gland in hexane elicited stronger oviposition reduction responses in C. cosyra than in B. dorsalis. These results suggest that ant gland compounds play a role in the oviposition avoidance behaviour of both fruit fly species. Moreover, both African fruit fly species and invasive Asian species, are repelled by Oecophylla longinoda semiochemicals implying that B. dorsalis experienced similar evolutionary pressures, and reacting to similar cues, from Oecophylla smaragdina in Asia as did C. cosyra from Oecophylla longinoda in Africa.
Keywords: African Research